Optimisation of Asphalt Extraction from Asbuton Using Microwave-Assisted Extraction (MAE) Method - Hikmayani; I W. Sutapa; Sahidin; L. O. Ahmad (International Journal of Acta Material, 2025)
Buton natural asphalt (Asbuton) is a strategic non petroleum bitumen resource with promising potential in road construction. However, conventional extraction methods such as Soxhlet and reflux suffer from long processing times, high energy demand, and excessive solvent use. This review evaluates Microwave-Assisted Extraction (MAE) as a green and efficient alternative for extracting bitumen from Asbuton. MAE employs rapid dielectric heating, enabling selective bitumen release while minimizing solvent consumption. Key process variables, including solvent polarity, solid-to-solvent ratio, temperature, extraction time, microwave power, and system pressure are critically reviewed. Comparative data show that MAE significantly improves extraction yield and operational efficiency. In addition, Response Surface Methodology (RSM) is discussed as a modeling tool to optimize variable interactions and identify ideal extraction conditions. Visual aids such as flow diagrams and comparative tables are used to clarify performance metrics and technical constraints. The review also outlines major challenges in MAE implementation, including microwave penetration in low-dielectric matrices and the need for scalable reactor designs. Overall, this paper provides a comprehensive perspective on MAE-based extraction for Asbuton, offering insight into its advantages, limitations, and directions for future research and industrial application.